Low-Radiation-Dose Stress Myocardial Perfusion Measurement Using First-Pass Analysis Dynamic Computed Tomography: A Preliminary Investigation in a Swine Model. Issue 12 (December 2019) - Hubbard, Logan; Malkasian, Shant; Zhao, Yixiao; Abbona, Pablo; Kwon, Jungnam; Molloi, Sabee
Abstract : Objectives: The aim of this study was to assess the feasibility of a prospective first-pass analysis (FPA) dynamic computed tomography (CT) perfusion technique for accurate low-radiation-dose global stress perfusion measurement. Materials and Methods: The prospective FPA technique was evaluated in 10 swine (42 ± 12 kg) by direct comparison to a previously validated retrospective FPA technique. Of the 10 swine, 3 had intermediate stenoses with fractional flow reserve severities of 0.70 to 0.90. In each swine, contrast and saline were injected peripherally followed by dynamic volume scanning with a 320-slice CT scanner. Specifically, for the reference standard retrospective FPA technique, volume scans were acquired continuously at 100 kVp and 200 mA over 15 to 20 seconds, followed by systematic selection of only 2 volume scans for global perfusion measurement. For the prospective FPA technique, only 2 volume scans were acquired at 100 kVp and 50 mA for global perfusion measurement. All prospective global stress perfusion measurements were then compared with the corresponding reference standard retrospective global stress perfusion measurements through regression analysis. The CTDIvol 32 and size-specific dose estimate of the prospective FPA technique were also determined. Results: All prospective global stress perfusion measurements (PPRO ) at 50 mA were in good agreement with the reference standard retrospective global stress perfusion measurements (PREF ) at 200 mA (PPRO = 1.07 PREF −0.09, r = 0.94; root-mean-square error = 0.30 mL/min per gram). The CTDIvol 32 and size-specific dose estimate of the prospective FPA technique were 2.3 and 3.7 mGy, respectively. Conclusions: Accurate low-radiation-dose global stress perfusion measurement is feasible using a prospective FPA dynamic CT perfusion technique.